2023
DOI: 10.1186/s12871-023-02206-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound-guided transversalis fascia plane block and anterior quadratus lumborum block in patients undergoing caesarean delivery: a randomized study

Abstract: Background Cesarean section is becoming increasingly common. Well-managed postoperative analgesia improves patient comfort while encouraging early ambulation and breastfeeding. The analgesic efficacy of transversalis facial plane block (TFPB) vs. anterior quadratus lumborum block (QLB) was compared in this study. Methods We analyzed the data of 49 pregnant women (gestation, ≥ 37weeks; age, 18–45years) scheduled for elective cesarean delivery (CD) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
(39 reference statements)
0
1
0
Order By: Relevance
“… 26 Bilgin et al compared transversalis fascia plane block and anterior QLB in patients undergoing caesarean delivery, and confirmed that anterior QLB significantly reduced postoperative visceral pain and opioid consumption. 27 The study by Jadon et al reported that anterior QLB prolonged the time to the first request for analgesics, reduced the dose of fentanyl, and effectively alleviated postoperative pain, however the analgesic effect of anterior QLB on visceral pain could not be verified, because the study did not differentiate between incisional pain and visceral pain, the analgesic effect of anterior QLB on visceral pain could not be confirmed. 28 Similarly, Dam et al also reported the anterior QLB significantly reduced postoperative opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Bilgin et al compared transversalis fascia plane block and anterior QLB in patients undergoing caesarean delivery, and confirmed that anterior QLB significantly reduced postoperative visceral pain and opioid consumption. 27 The study by Jadon et al reported that anterior QLB prolonged the time to the first request for analgesics, reduced the dose of fentanyl, and effectively alleviated postoperative pain, however the analgesic effect of anterior QLB on visceral pain could not be verified, because the study did not differentiate between incisional pain and visceral pain, the analgesic effect of anterior QLB on visceral pain could not be confirmed. 28 Similarly, Dam et al also reported the anterior QLB significantly reduced postoperative opioid consumption.…”
Section: Discussionmentioning
confidence: 99%